Asymptomatic screening for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) as an infection prevention measure in healthcare facilities: Challenges and considerations. (21st December 2022) - Talbot, Thomas R.; Hayden, Mary K.; Yokoe, Deborah S.; Malani, Anurag N.; Amer, Hala A.; Kalu, Ibukunoluwa C.; Logan, Latania K.; Moehring, Rebekah W.; Munoz-Price, Silvia; Palmore, Tara N.; Weber, David J.; Wright, Sharon B.
Executive summary: Testing of asymptomatic patients for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) (ie, "asymptomatic screening) to attempt to reduce the risk of nosocomial transmission has been extensive and resource intensive, and such testing is of unclear benefit when added to other layers of infection prevention mitigation controls. In addition, the logistic challenges and costs related to screening program implementation, data noting the lack of substantial aerosol generation with elective controlled intubation, extubation, and other procedures, and the adverse patient and facility consequences of asymptomatic screening call into question the utility of this infection prevention intervention. Consequently, the Society for Healthcare Epidemiology of America (SHEA) recommends against routine universal use of asymptomatic screening for SARS-CoV-2 in healthcare facilities. Specifically, preprocedure asymptomatic screening is unlikely to provide incremental benefit in preventing SARS-CoV-2 transmission in the procedural and perioperative environment when other infection prevention strategies are in place, and it should not be considered a requirement for all patients. Admission screening may be beneficial during times of increased virus transmission in some settings where other layers of controls are limited (eg, behavioral health, congregate care, or shared patient rooms), but widespread routine use of admission asymptomatic screening is not recommended over strengthening other infection prevention controls. In this commentary, we outline the challenges surrounding the use of asymptomatic screening, including logistics and costs of implementing a screening program, and adverse patient and facility consequences. We review data pertaining to the lack of substantial aerosol generation during elective controlled intubation, extubation, and other procedures, and we provide guidance for when asymptomatic screening for SARS-CoV-2 may be considered in a limited scope.